2020
DOI: 10.1155/2020/8528976
|View full text |Cite
|
Sign up to set email alerts
|

Association of NCF2, NCF4, and CYBA Gene Polymorphisms with Rheumatoid Arthritis in a Chinese Population

Abstract: Objective. Recent studies have focused on the special roles of NADPH-oxidase in multiple autoimmune diseases. Nevertheless, the association of genetic variation in NADPH-oxidase genes with rheumatoid arthritis (RA) was not extensively studied in a Chinese population. We performed this study to examine the association of NCF2, NCF4, and CYBA gene polymorphisms with RA susceptibility in a Chinese population. Methods. Six single nucleotide polymorphisms (SNPs) (NCF2 rs10911363, NCF4 rs1883112, rs4821544, rs729749… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Nevertheless, a copy number variation in NCF1 has been found associated with RA [ 11 ]. In addition, it was also found that SNPs linked to the NCF4 gene was associated with RA [ 13 , 14 ]. These findings confirm previous discoveries in animal models, where Ncf1 was found to be major gene controlling both arthritis [ 15 , 16 ] and lupus [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a copy number variation in NCF1 has been found associated with RA [ 11 ]. In addition, it was also found that SNPs linked to the NCF4 gene was associated with RA [ 13 , 14 ]. These findings confirm previous discoveries in animal models, where Ncf1 was found to be major gene controlling both arthritis [ 15 , 16 ] and lupus [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among these, NCF4 has been proven to regulate the production of intracellular ROS by inducing the NOX complex to phagosome membranes through the binding of phosphatidylinositol 3-phos-phate. In this regard, Zhang TP et al demonstrated that gene polymorphisms of NCF4 rs4821544 and rs729749, but not of NCF2 and CYBA, contribute to RA susceptibility (12). In parallel to gene polymorphisms, epigenetic mechanisms, including DNA methylation, histone modifications, and small (s) and long (l) non-coding RNAs (ncRNA) play important roles in mechanisms underlying RA pathogenesis.…”
Section: Genetic Aspectsmentioning
confidence: 99%
“…A neutrophil cytosolic factor 1 ( NCF1 ) polymorphic allele, which causes a low reactive oxygen response, has been shown to be a causative factor in SLE and possibly also in RA [ [2] , [3] , [4] ]. Associations between RA and single nucleotide polymorphisms (SNP) in the NCF4 gene have also been identified [ 2 , 5 ]. Both NCF1 and NCF4 are components of the NADPH oxidase type 2 (NOX2) complex, which is known to be responsible for the induced production of reactive oxygen species (ROS) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%